Influence of Upper-Extremity and Lower-Extremity Resistance Exercise on Segmental Body Composition and Body Fluid Estimates. Issue 5 (17th May 2023) - Rodriguez, Christian; Florez, Christine M.; Prather, Jessica; Zaragoza, Javier; Tinnin, Matthias; Brennan, Kindyle L.; Taylor, Lem; Tinsley, Grant M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Rodriguez, C, Florez, CM, Prather, J, Zaragoza, J, Tinnin, M, Brennan, KL, Taylor, L, and Tinsley, GM. Influence of upper-extremity and lower-extremity resistance exercise on segmental body composition and body fluid estimates. J Strength Cond Res 37(5): 1042–1051, 2023—The purpose of this analysis was to determine if acute, localized resistance exercise (RE) artificially influences total and regional estimates of body composition from dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis (BIA). Recreationally active male ( n = 14) and female ( n = 18) subjects completed 3 testing visits: rest (R), upper-extremity RE (U), and lower-extremity RE (L). Dual-energy X-ray absorptiometry scans were completed before exercise and 60 minutes after exercise. Bioelectrical impedance analysis was completed immediately before and after exercise and at 15, 30, and 60 minutes after exercise. Subjects were not allowed to intake fluid during the exercise session or during the postexercise assessment period. The effects of the acute RE session on DXA and BIA estimates were analyzed using linear mixed-effects models with a random intercept for subject. Condition by time interactions were observed for most BIA outcomes. Relative to the reference model (i.e., R condition at baseline), total body water and fat-free mass estimates were, on average, approximately 1 and approximately 1.2 kg higher, in the U condition. In contrast, lower-extremity RE exerted little or no impact on most BIA variables. Some DXA estimates exhibited time main effects, but the magnitude of changes was negligible. An acute bout of localized RE, particularly upper-extremity RE, can artificially influence BIA body fluid and composition estimates, whereas DXA may be robust to the acute biological error introduced by RE. Although body composition assessments should ideally be conducted under standardized conditions, DXA may be suitable in less standardized situations. In addition, BIA is differentially influenced by upper-extremity and lower-extremity resistance exercise.